Peran Bidan Dalam Pelaksanaan Permenkes Nomor 53 Tahun 2014 Tentang Pelayanan Kesehatan Neonatal Pada Bayi Baru Lahir Di Puskesmas Kaleroang Sulawesi Tengah - Sri Lestari Ningsih; A Widanti S; Suwandi Suwandi (SOEPRA, 2018)
Health development is an effort undertaken by all components of the nation to increase awareness, willingness and ability to live healthily Midwifery services is an integral service of health care system. A Midwife is one health worker who has an important and strategic position, especially in reducing the number of infant deaths Newborn. The purpose of this research is to know the role of the midwife in giving health service t a newborn baby based on Permenkes Number 53 the Year 2014 About neonatal health service the newborn.This research is a sociological Juridical research with analytic descriptive research specification. This research uses primary data and secondary data. Method of collecting primary data through the interview to respondent and resource person. The respondents consisted of 10 midwives who worked at Kaleroang Community Health Center and the parents of newborns 10 people. While the speakers consisted of Head of Puskesmas Kaleroang, village cadres. Secondary data obtained through literature study which then analyzed qualitatively.Implementation of the role of midwives in providing neonatal health services to newborns only 4 midwives who have done their job thoroughly and 6 midwives have not done their job. And has not accomplished his duties as an implementer and educator. The role of the midwife as the implementer has not done the newborn care in the neonatal period (0-28 days), and the umbilical cord care. While the role of midwives as educators has not provided counseling and breastfeeding counseling, as well as the fostering of community participation in the field of maternal and child health. The supporting factors are Puskesmas, Puskesmas Pembantu, and Posyandu. While the inhibiting factors are the lack of health personnel (midwives), inadequate transportation facilities, the lack of midwifery knowledge so that the skills are still low, and the health equipment in some villages is not yet complete